Expressão do valor genérico nos provérbios portugueses e croatas - Lanović, Nina (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2022)
Starting from the hypothesis that proverbs represent prototypes of generic sentences and considering that, in our view, they have not been properly studied in the field of linguistics (especially Croatian linguistics), we propose in this work to reflect on the mechanisms that convey the generic value of proverbs. We believe that the generic interpretation in a proverbial context arises from the interaction of several factors – from the linguistic (semantic-pragmatic) ones to certain conceptual mechanisms. At the linguistic level, genericity is actualized in the behavior of several grammatical categories, from nouns and noun phrases, adverbial adjuncts, determiners and quantifiers, and temporal, aspectual and modal values, to the interpropositional relations that represent “type-situations”. For the purposes of this work, we focused on the noun phrase (in the subject position), an aspect that we find relevant even in terms of comparing Portuguese and Croatian proverbial texts, due to the differences between these two languages in the expression of the category (in)determination. The problematization of the properties of the subject noun phrase necessarily requires considering the semantic nature of predications. Since genericity is a linguistic, but also a logical and conceptual “universal”, we propose to investigate the mechanisms in which it is actualized in (European) Portuguese and Croatian proverbs